Defect depth effects in Pulsed Eddy Current thermography - Hong Zhang; Guiyun Tian; Yunze He; Xianzhang Zuo (2011 17th International Conference on Automation and Computin, 2011)
In recent years, there has been an increasing interest in crack detecting and locating using Pulsed Eddy Current (PEC) thermography. PEC thermographic is an emerging integrative non-destructive testing (NDT) with the ability to inspect defects over large areas. The heating and diffusing results can be obtained easily and quickly from a thermal camera. In this paper, numerical modeling and experimental studies are applied to understand depth and tip effect on PEC thermography with different depths of defects, including transient heating propagation and magnetic flux distribution. This fundamental understanding of transient heating propagation and magnetic flux distribution will aid in the development of feature extraction and pattern recognition techniques for the quantitative analysis of PEC thermography images and crack characterisation.